Direct measurement of diffusion length in mixed lead-halide perovskite films using scanning photocurrent microscopy - Kim, Ahram; Son, Byung Hee; Kim, Hwan Sik; Ahn, Yeong Hwan (Current Optics and Photonics, 2018)
Carrier diffusion length in the light-sensitive material is one of the key elements in improving the light-current conversion efficiency of solar-cell devices. In this paper, we measured the carrier diffusion length in lead-halide perovskite (MAPbI3) and mixed lead-halide (MAPbI3-xClx) perovskite devices using scanning photocurrent microscopy (SPCM). The SPCM signal decreased as we moved the focused laser spot away from the metal contact. By fitting the data with a simple exponential curve, we extracted the carrier diffusion length of each perovskite film. Importantly, the diffusion length of the mixed-halide perovskite was higher than that of the halide perovskite film by a factor of 3 to 6; this is consistent with the general expectation that the carrier mobility will be higher in the case of the mixed lead-halide perovskites. Finally, the diffusion length was investigated as a function of applied bias for both samples, and analyzed successfully in terms of the drift-diffusion model.
Keywords: Carrier diffusion length; Current conversion efficiency; Diffusion length; Direct measurement; Drift-diffusion model; Halide perovskites; Scanning photocurrent microscopies; Solar cell devices; Diffusion length; Perovskites; Scanning photocurrent microscopy